2004
DOI: 10.17221/5708-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

An attitude of veterinary practitioners towards animal rights in Turkey

Abstract: ABSTRACT:The authors examined the a�itudes of veterinary practitioners in Turkey towards animals' right to life. For this purpose, a telephone questionnaire was applied on a total of 303 practitioners located in four provinces in Turkey. The overall response rate was 82%. The respect for right to life was valued slightly over neutral. According to the 5-point Likert scale, the average value scored by the participants for the items of views about animals' right to life was found as 3.25. Type of practice (pet c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 4 publications
(4 reference statements)
2
1
0
1
Order By: Relevance
“…Likewise, the results of this study indicated that both the students and educators from Istanbul, where the industry is important and which has characteristics of a metropolis, showed an a�itude closer to the zoo-centric line than the students from other cities (Konya and Elazig). This was also in parallel with the results of Pifer et al (1994) and Ozen et al (2004). In a few studies carried out on the undergraduate students of medicine, veterinary and other departments, most of the participants stated that AUR was acceptable in terms of moral aspect (Hagelin et al, 1999(Hagelin et al, , 2000.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Likewise, the results of this study indicated that both the students and educators from Istanbul, where the industry is important and which has characteristics of a metropolis, showed an a�itude closer to the zoo-centric line than the students from other cities (Konya and Elazig). This was also in parallel with the results of Pifer et al (1994) and Ozen et al (2004). In a few studies carried out on the undergraduate students of medicine, veterinary and other departments, most of the participants stated that AUR was acceptable in terms of moral aspect (Hagelin et al, 1999(Hagelin et al, , 2000.…”
Section: Discussionsupporting
confidence: 69%
“…The gender is the primary reason to show a definite trend in most of the studies aiming to determine an a�itude towards the animal rights and AUR, and females represent a more zoo-centric trend than males in these ma�ers (Gallup and Beckstead, 1988;Herzog et al, 1991;Driscoll, 1992;Broida et al, 1993;Furnham and Heyes, 1993;Eldridge and Gluck, 1996;Pifer, 1996;Ozen et al, 2004). The results of this study also proved that the female participants were closer to the zoo-centric line than males in both the groups of the educators and the students.…”
Section: Discussionsupporting
confidence: 67%
“…In Italy and other countries, veterinarians take a professional oath, swearing to use their skills and knowledge for the benefit of animal health and welfare. Attitudes toward animals are important in influencing the way animals are treated [2], and several studies have indicated how a variety of factors, such as gender [3,4], disease state [5], professional discipline [6], perceived responsibility, keeping of a pet, membership in a society [4], and country of residence [7] may influence attitudes and sensitivities of a veterinary practitioner toward animal welfare issues.…”
Section: Introductionmentioning
confidence: 99%
“…Bu çerçevede, çalışmada elde edilen sonuçların literatürle uyumlu olduğu görülmektedir. Hayvan kullanımı, insan-hayvan birlikteliği ve yansımaları konularında yapılan çalışmalarda pet sahipliğinin, hayvanlara yönelik tutum ve davranışlar üzerinde olumlu etkiye sahip bir faktör olduğu bildirilmektedir (11,13,14). Bu çalışmanın sonuçları da, pet sahipliği ve evde köpek besleme isteği değişkenlerinin hayvanlara yaklaşıma olumlu etkileri konusunda literatürle paralellik göstermektedir.…”
Section: Tartışma Ve Sonuçunclassified